Antagonistic control of intracellular signals by EpOMEs in hemocytes induced by PGE2 and their chemical modification for a potent insecticide - Niayesh Shahmohammadi; Shiva Haraji; Falguni Khan; Åshild Moi Sørskår; Parastoo Ebrahimi Danielsen; Anders Vik; Yonggyun Kim (PLoS ONE, 2025)
During an infection, prostaglandin E2 (PGE2) mediates immune responses in insects and later epoxyoctadecamonoenoic acids (EpOMEs) are produced from linoleic acid to suppress excessive and unnecessary immune responses. Intracellular signaling pathway by which these oxylipins suppress the immune responses was previously unclear. This study demonstrated that EpOMEs antagonize the secondary messengers induced by PGE2 in a lepidopteran species, Maruca vitrata. PGE2 injections significantly increased hemocyte-spreading behavior, along with raised calcium ion and cAMP levels in hemocytes, and also up-regulated phenoloxidase activity and expressions of antimicrobial peptides. These cellular and humoral immune responses induced by PGE2 were dose-dependently inhibited by EpOMEs, with 12,13-EpOME being more effective than 9,10-EpOME in immunosuppression. PGE2 treatment also elevated the total number of circulating hemocytes, with the majority (88.4%) of these increased hemocytes being granulocytes. Conversely, EpOMEs suppressed the up-regulation of total hemocyte count induced by PGE2 and directly reduced the total hemocyte count by inducing apoptosis in granulocytes, as visualized by the TUNEL assay. These immunosuppressive and cytotoxic effects suggest the potential of EpOME as a lead compound for developing a novel type of insecticides. To chemically stabilize EpOMEs, the epoxide group was replaced with a propoxide group, and the carboxylic terminal was methylated. The 12-propoxyl regioisomer was selected based on immunosuppressive bioassays. Further investigation of the two possible enantiomers of 12-propoxyl regioisomer showed that the 12R-enantiomer was more effective than the 12S-enantiomer in immunosuppression. The resulting 12R-propoxy octadecamonoenoic methyl ester displayed insecticidal activities at low nanogram levels per insect by hemocoelic injection and at <  50 ppm by the leaf-dipping method against three lepidopteran insects.